ভাষা-সাহিত্য-সংস্কৃতি বিতান - (:unkn) unknown (My University, 2019)
It began its journey with several units of research such as Tribal and Border Languages, Sociolinguistics, Phonetics, Psycholinguistics, Material Production and Training, Testing and Evaluation, Educational Technology, Lexicography and Translation, Cartography, Folklore and Computer Applications.
Bhasha-Sahitya-Sanskriti Bitan
Keywords: Assamese